Functional analysis of N-acetylglucosaminyltransferase-I knockdown in 2D and 3D neuroblastoma cell cultures. - M Kristen Hall (Public Library of Science (PLoS), 2021)
Tumor development can be promoted/suppressed by certain N-glycans attached to proteins at the cell surface. Here we examined aberrant neuronal properties in 2D and 3D rat neuroblastoma (NB) cell cultures with different N-glycan populations. Lectin binding studies revealed that the engineered N-glycosylation mutant cell line, NB_1(-Mgat1), expressed solely oligomannose N-glycans, and verified that the parental cell line, NB_1, and a previous engineered N-glycosylation mutant, NB_1(-Mgat2), expressed significant levels of higher order N-glycans, complex and hybrid N-glycans, respectively. NB_1 grew faster than mutant cell lines in monolayer and spheroid cell cultures. A 2-fold difference in growth between NB_1 and mutants occurred much sooner in 2D cultures relative to that observed in 3D cultures. Neurites and spheroid cell sizes were reduced in mutant NB cells of 2D and 3D cultures, respectively. Cell invasiveness was highest in 2D cultures of NB_1 cells compared to that of NB_1(-Mgat1). In contrast, NB_1 spheroid cells were much less invasive relative to NB_1(-Mgat1) spheroid cells while they were more invasive than NB_1(-Mgat2). Gelatinase activities supported the ranking of cell invasiveness in various cell lines. Both palladin and HK2 were more abundant in 3D than 2D cultures. Levels of palladin, vimentin and EGFR were modified in a different manner under 2D and 3D cultures. Thus, our results support variations in the N-glycosylation pathway and in cell culturing to more resemble in vivo tumor environments can impact the aberrant cellular properties, particularly cell invasiveness, of NB.